The neuroprotective effects of curcumin are associated with the regulation of the reciprocal function between autophagy and HIF-1α in cerebral ischemia-reperfusion injury - Hou Y; Wang J; Feng J (Dove Medical Press, 2019)
Yang Hou, Jue Wang, Juan Feng Department of Neurology, Shengjing Hospital of China Medical University, Shenyang, Liaoning 110004, People’s Republic of China Purpose: The beneficial, neuroprotective effects of curcumin against ischemia-reperfusion injury have been demonstrated. In the present study, whether curcumin exerts neuroprotective effects associated with the inhibition of autophagy and hypoxia inducible factor-1α (HIF-1α) was investigated. Materials and methods: PC12 cellular model of oxygen glucose deprivation/reperfusion (OGD/R) has been developed to mimic cerebral ischemia-reperfusion injury. Cell viability was evaluated using the CellTiter 96® AQueous One Solution Cell Proliferation Assay. Apoptosis was assessed using flow cytometry. The expression levels of HIF-1α and autophagy-associated proteins, LC3 and P62, were examined using Western blot. The autophagy flux was quantitatively estimated based on the number of autophagic compartments using fluorescence microscopy. In addition, 3-methyladenine (3-MA) was administered to PC12 cells to investigate how autophagy affects HIF-1α. Moreover, the inhibitory effects of HIF-1α on autophagy activation level were examined. Results: In this study, curcumin decreased the death and apoptosis of cells, and inhibited autophagy and HIF-1α under OGD/R conditions, consistent with 3-MA treatment or HIF-1α downregulation. Moreover, inhibition of autophagy caused a decrease in HIF-1α, and the attenuation of HIF-1α induced autophagy suppression under OGD/R conditions. Conclusion: The results of this study showed that curcumin exerts neuroprotective effects against ischemia-reperfusion, which is associated with the regulation of the reciprocal function between autophagy and HIF-1α. Keywords: curcumin, cerebral ischemia-reperfusion, autophagy, hypoxia inducible factor-1α